Cognitive Dissonance pada Konteks Berkomunikasi dan Mencari Informasi di Ruang Digital: Fenomena Selective Exposure - Fadhila Hasna Athaya (JURNAL LENSA MUTIARA KOMUNIKASI, 2022)
In the digital space that is now increasingly dominating our lives, there are challenges and new social situations that require us to adapt. Cognitive Dissonance Theory (CDT) places a focus on seeing human behavior in situations that are incompatible with the cognition he has. After six decades of CDT's existence, there have been many derivative concepts that can be used to analyze causation in this dissonance situation. Selective exposure is a concept derived from CDT that has received attention from researchers in analyzing the phenomenon of filter bubbles and echo chambers. To examine the application of CDT in a contemporary context, in this digital space, this study was conducted by making a literature review that focuses on elaborating on the theory and context of CDT in use. Using qualitative content analysis from a collection of previous studies, this study maps the relevance of theory to the context of situations in the digital space. The conclusion is that CDT, both based on basic assumptions and derived concepts tested by other researchers, can objectively predict the cause-and-effect of a situation that triggers dissonance in a person's cognition when a situation with similar conditions occurs.